Evaluasi Tingkat Kematangan Tata Kelola Layanan TI pada UPA-TIK Universitas Sam Ratulangi Menggunakan Framework ITIL 4 - Rafael Rivelino Lalujan; Sherwin R.U.A. Sompie; Steven Ray Sentinuwo (Riau Jurnal Teknik Informatika, 2026)
Information Technology (IT) governance plays a vital role in ensuring the alignment between IT services and institutional objectives. This study aims to evaluate the maturity level of IT governance at the Information and Communication Technology Support Unit (UPA-TIK) of Sam Ratulangi University using the ITIL 4 framework. The evaluation was conducted across 16 ITIL 4 management practices using a mixed-methods approach, combining quantitative surveys, qualitative interviews, and document validation. The findings indicate that 15 practices achieved Maturity Level 3 (Defined), while one practice, namely Continual Improvement, reached Level 4 (Managed). Gap analysis based on the Four Dimensions of Service Management revealed that the limited adoption of a centralized Information Technology Service Management (ITSM) system, reliance on informal communication channels such as WhatsApp for incident reporting, inconsistent operational documentation, and high dependency on vendors for hardware recovery are the primary factors hindering maturity improvement. Based on these findings, this study proposes a strategic implementation roadmap aligned with the five Digital Transformation Strategic Programs (PSTD) of Sam Ratulangi University for the 2024–2028 period. The study contributes by providing a more evidence-based foundation for strategic decision-making in IT governance and IT service management, thereby supporting service quality improvement and accelerating the university's digital transformation initiatives.